COLLECTION MANAGEMENT OF THE AR-RAUDLATUL HASANAH MEDAN MODERN LIBRARY IN SUPPORTING SCIENTIFIC DEVELOPMENT - Aliza, Muthia; Yusniah, Yusniah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study aims to describe and analyze the collection management at the Library of Pesantren Modern Ar-Raudlatul Hasanah Medan in supporting the scientific development of students. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. The findings indicate that the collection acquisition process is strategically carried out through purchases (80%) and endowments (20%), with a focus on Islamic and general collections relevant to the curriculum. The collections are organized based on a specific classification system and maintained through rebinding efforts. The library also implements various literacy programs such as mobile libraries, reading carts, literacy competitions, and student study groups to enhance students’ literacy and critical thinking skills. However, challenges remain, including limited library staff and the students’ tight schedules, which hinder the optimal implementation of literacy activities. The library plays a vital role in supporting the learning process but requires additional resources and extended operating hours to function more effectively as a center for literacy and intellectual development in the pesantren environment.